A Robust Distributed Adaptive Finite Element Program for Coupled Fluid-Structure Problems - De Santiago, E.; Law, K. H. (Engineering with computers, 1999)
This paper describes an implementation of an adaptive finite element program for coupled fluid-structure problems using a network of workstations. A pool of task programming paradigm suitable for a heterogeneous distributed workstation environment is presented. The issues of load balancing and fault recovery are explored. Numerical results for this distributed programming paradigm are presented and compared with sequential and parallel programming models.